304 Transgenerational influence of prenatal stress on temperament, birth weight, and weaning weight of Brahman calves. (5th December 2019) - Littlejohn, Brittni P; Riley, David G; Neuendorff, Don A; Long, Charles R; Welsh, Thomas H; Randel, Ronald D
Abstract: The objective was to evaluate the transgenerational influence of prenatal transportation stress (PNS) on temperament, birth weight, and weaning weight in Brahman calves. Dams were derived from multiparous cows that were transported for 2 h at 60, 80, 100, 120, and 140 d of gestation (n = 48) or maintained as Controls (n = 48). Heifers born to Transported or Control cows were followed through maturity and their calves (n = 79; 35 calves born to Control dams and 44 to PNS dams) studied across multiple years. Calf birth and weaning weights were recorded. Calf temperament at weaning was evaluated utilizing pen score (PS; 1=calm and 5=excitable), exit velocity (EV; m/sec), and temperament score (TS; (PS+EV)/2). Data were analyzed using mixed linear models. Fixed effects included dam treatment, calf sex, and birth season nested within birth year (season nested within year was identified as an efficient parameterization). Calf sire was a random effect. Birth weight was not affected by dam treatment, calf sex, or season nested within year (P > 0.1). Weaning weight was greater in males than females (P < 0.01). Weaning weight was affected by season nested within year (P < 0.01). DOA at weaning was a covariate for weaning weight (0.74±0.09 kg; P < 0.01), but not PS, EV, or TS (P < 0.1). Weaning weight was not affected by dam treatment (P > 0.1). TS was affected by season nested within year (P = 0.04) but not dam treatment or calf sex (P > 0.1). EV was not affected by dam treatment, calf sex, or season nested within year (P > 0.1). PS was affected by season nested within year (P < 0.01) but not calf sex (P > 0.1). Calves born to PNS dams had greater (P = 0.02) PS than calves born to Controls (3.17±0.20 and 2.58±0.22, respectively). There was a transgenerational influence of PNS on temperament but not birth or weaning weight.